Socialization of Business Creation and Utilizing Social Media as a Product Marketing Strategy at Perum Kopti, East Jakarta - Darmeinis, Darmeinis; Siahaan, Leroy Holman; Agustina, Silvia; Prasetyo, Reinaldo; Ardyaputri, Syafa Kamila; Budiarti, Rizka Wahyu; Wulandari, Yayang; Saputra, Feri Ragil (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of these obligations as a student of Panca Sakti University Bekasi will carry out Community Service, this is carried out in connection with concerns about following technological developments and advances, especially Indonesia as a country that has a lot of natural and human resource potential that cannot be equated with developed countries. this concern is by organizing Community Service activities in the form of